MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA MELALUI BAHAN AJAR BERNUANSA STEM DENGAN MODEL PBL - Illaya Salsabila, Hanna; Hendikawati, Putriaji (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
Problem solving ability is an important aspect of mathematical abilities that students must have. The ability to solve problems is important for students to achieve the main goals in learning mathematics. In reality, problem solving skills have not been mastered well by most students at school. One effort that can be made to help students improve problem solving abilities is to improve the learning tools used, such as teaching materials. This article aims to develop STEM themed teaching materials with a PBL model to help students improve their problem-solving abilities. This research uses the Research and Development method with a 4D model, but the researcher will only carry out the 2D stage, namely definition and design. Applying the STEM approach can help students practice problem solving skills in dealing with problems that occur in everyday life by combining four disciplines, namely science, technology, engineering and mathematics. Problem Based Learning encourages students to be able to find solutions to the problems they face in everyday life, so that it can help them to develop problem-solving abilities. Furthermore, research can be carried out by continuing the stages that have not been carried out, namely developing and disseminating, so that appropriate and effective teaching materials can be produced to help students improve their problem-solving abilities.